Islam, religious liberty and constitutionalism in Europe - Hill, Mark 1965-; Papadopulu, Triantaphyllia 1971- (Hart Publishing, Bloomsbury Publishing Plc, 2024)
"Taking a close and critical look at Muslim practice and Islamic belief within the prevailing legal and political frameworks in Europe, this book focuses on constitutional challenges, religious freedom and other human rights, and securitisation and Islamophobia"--
Keywords: Islam; Religionspolitik; Religionsfreiheit; Konstitutionalismus; Europa; Aufsatzsammlung